Factors associated with the frequency of manic and depressive episodes in bipolar disorder: a multicenter study in China - Shuang Liu; Jin-Jie Xu; Xue-Quan Zhu; Bing-Bing Fu; Yan-Li Pan; Cong-Cong Sun; Sheng Li; Gao-Ming Xie; Ling Zhang (BMC Psychiatry)
Abstract Background Mania and depression are the predominant mood episodes in bipolar disorder (BD), and their frequency significantly affects the long-term prognosis of patients. Method This is a multicenter, longitudinal cohort study in China. Sociodemographic and clinical characteristics of patients were statistically analyzed. Poisson regression analyses were performed to identify factors associated with the frequency of manic and depressive episodes. Results A total of 520 BD patients were enrolled in this study. Poisson regression model analysis showed that shorter years of education (OR = 1.03, P = 0.03), mixed polarity of the first episode compared to mania (OR = 2.33, P < 0.01) or depression (OR = 1.79, P = 0.01), earlier age at diagnosis (OR = 1.03, P = 0.01), comorbid substance use disorder (OR = 1.41, P = 0.02), presence of psychotic symptoms (OR = 1.18, P = 0.04), use of antidepressant medication (OR = 1.52, P = 0.01), and non-use of mood stabilizers (OR = 1.57, P<0.01) are positively associated with the frequency of manic episodes. Being male (OR = 1.22, P = 0.01), the use of mood stabilizers (OR = 1.47, P<0.01) and a diagnosis of bipolar II disorder (BD-II) compared to bipolar I disorder (BD-I) (OR = 1.27, P = 0.01) are positively associated with the frequency of depressive episodes. Conclusion The study highlights the critical association of clinical and sociodemographic factors with the frequency of manic and depressive episodes in BD patients. Addressing these factors may improve long-term outcomes for individuals with bipolar disorder.